Learn Python in five minutes with Colab Notebook. (Pragmatic AI Solutions, 2022)
Learn Python in five Minutes with Colab Notebook. Covers statements, lists, dictionaries, and for loops. 00:00 Intro 00:25 Using Colab 00:40 Tables of Contents in Colab 00:55 Save copy in Github 01:05 Print hello world 01:24 print equation 01:50 Using f-strings to print 02:05 using list data structures 02:20 Appending to a list 02:45 Looping with for loops in Python 03:30 Pushing to a list 04:00 Random Pushing to a container 05:19 Using a dictionary in Python.